ADRB2 is regulated by TRIM22 and facilitates lung adenocarcinoma progression via JAK2/STAT3 signaling pathway - Mingming Xu; Song Han; Mingjun Yang; Jianle Chen; Yifei Liu; Youlang Zhou; Jiahai Shi (Scientific Reports)
Abstract Lung adenocarcinoma (LUAD) is the most common pathological subtype of lung cancer. Adrenergic signal has always been considered as an important link with the occurrence and development of cancer. Considerable evidence suggests that β-2 adrenergic receptor (ADRB2) shows an important role in regulating many types of human cancer. But the role of ADRB2 in LUAD is still uncovered. To elucidate the expression of ADRB2 in LUAD, a comprehensive analysis was conducted utilizing the GEO database, quantitative reverse transcription polymerase chain reaction (qRT-PCR), western blot, and immunohistochemistry on human LUAD tissue samples. Subsequent to the modulation of ADRB2 expression in various LUAD cell lines, assessments of cell viability, invasion, and migratory capacity were performed using the Cell Counting Kit-8 (CCK8) assay and transwell chamber assays, respectively. Furthermore, Gene Set Enrichment Analysis (GSEA) was employed to identify relevant pathways, which were subsequently validated through western blot analysis. Furthermore, the STRING database was utilized to predict that TRIM22 is the most significant interacting protein of ADRB2, a finding subsequently validated through immunoprecipitation assays. The cell cycle was analyzed using flow cytometry. The upregulated expression of ADRB2 observed in datasets GSE11969 and GSE68465 was corroborated by analyses of human LUAD tissues and was found to be associated with advanced disease stages. Overexpression of ADRB2 in A549 cells led to increased cell proliferation, migration, and invasion, which were associated with the activation of the JAK2/STAT3 signaling pathway. However, suppressing ADRB2 expression in H1299 cells resulted in reduced cell proliferation, migration, and invasion. Mechanistically, TRIM22 was found to interact with ADRB2, and negatively regulated ADRB2 expression and JAK2/STAT3 signaling pathway. Moreover, inhibition of the JAK2/STAT3 signaling pathway significantly affected cell cycle and suppressed cell proliferation in LUAD cells. Our findings suggest that weakened TRIM22 increased ADRB2 that activated the JAK2/STAT3 signaling pathway, thereby promoting LUAD development.